2019
DOI: 10.3389/fpsyg.2019.02463
|View full text |Cite
|
Sign up to set email alerts
|

Spelling in Deaf, Hard of Hearing and Hearing Children With Sign Language Knowledge

Abstract: What do spelling errors look like in children with sign language knowledge but with variation in hearing background, and what strategies do these children rely on when they learn how to spell in written language? Earlier research suggests that the spelling of children with hearing loss is different, because of their lack of hearing, which requires them to rely on other strategies. In this study, we examine whether, and how, different variables such as hearing degree, sign language knowledge and bilingualism ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 53 publications
(70 reference statements)
3
15
0
1
Order By: Relevance
“…The same study also suggested that there is a transfer from sign language and fingerspelling to writing: the sign-print bilingual DHH children were found to use some letters incorrectly in a word, because they were misled by the corresponding sign that happened to have this letter as handshape. This phenomenon was, however, not found among the bimodal bilingual DHH and CODA group using spoken and sign language (Gärdenfors et al 2019).…”
Section: Bimodal Bilingual Studies Of the Dhh And Coda Groupmentioning
confidence: 57%
See 4 more Smart Citations
“…The same study also suggested that there is a transfer from sign language and fingerspelling to writing: the sign-print bilingual DHH children were found to use some letters incorrectly in a word, because they were misled by the corresponding sign that happened to have this letter as handshape. This phenomenon was, however, not found among the bimodal bilingual DHH and CODA group using spoken and sign language (Gärdenfors et al 2019).…”
Section: Bimodal Bilingual Studies Of the Dhh And Coda Groupmentioning
confidence: 57%
“…The DHH group has repeatedly been reported to write fewer words, in the form of shorter texts compared to their monolingual and bilingual hearing peers. This is thought to be caused by a smaller vocabulary and a limited auditory input (e.g., Arfé et al 2016;Gärdenfors et al 2019;Oliveira et al 2020).…”
Section: Written Productmentioning
confidence: 99%
See 3 more Smart Citations